Lymph node metastasis is not associated with survival in patients with clinical stage T4 esophageal squamous cell carcinoma undergoing definitive radiotherapy or chemoradiotherapy - Zhu, Liqiong; Zhao, Zongxing; Liu, Ao; Wang, Xin; Geng, Xiaotao; Nie, Yu; Zhao, Fen; Li, Minghuan (Frontiers in Oncology, 2022)
Background Clinical T4 stage (cT4) esophageal tumors are difficult to be surgically resected, and definitive radiotherapy (RT) or chemoradiotherapy (dCRT) remains the main treatment. The study aims to analyze the association between the status of lymph node (LN) metastasis and survival outcomes in the cT4 stage esophageal squamous cell carcinoma (ESCC) patients that underwent treatment with dCRT or RT. Methods This retrospective study analyzed the clinical data of 555 ESCC patients treated with dCRT or RT at the Shandong Cancer Hospital and the Liaocheng People’s Hospital from 2010 to 2017. Kaplan–Meier and Cox regression analyses was performed to determine the relationship between LN metastasis and survival outcomes of cT4 and non-cT4 ESCC patients. The chi-square test was used to evaluate the differences in the local and distal recurrence patterns in the ESCC patients belonging to various clinical T stages. Results The 3-year survival rates for patients with non-cT4 ESCC and cT4 ESCC were 47.9% and 30.8%, respectively. The overall survival (OS) and progression-free survival (PFS) rates were strongly associated with the status of LN metastasis in the entire cohort (all P < 0.001) and the non-cT4 group (all P < 0.001) but not in the cT4 group. The local recurrence rates were 60.7% for the cT4 ESCC patients and 45.1% for the non-cT4 ESCC patients (P < 0.001). Multivariate analysis showed that clinical N stage (P = 0.002), LN size (P = 0.007), and abdominal LN involvement (P = 0.011) were independent predictors of favorable OS in the non-cT4 group. However, clinical N stage (P = 0.824), LN size (P = 0.383), and abdominal LN involvement (P = 0.337) did not show any significant correlation with OS in the cT4 ESCC patients. Conclusions Our data demonstrated that the status of LN metastasis did not correlate with OS in the cT4 ESCC patients that received dCRT or RT. Furthermore, the prevalence of local recurrence was higher in the cT4 ESCC patients.